2021
DOI: 10.48550/arxiv.2103.11608
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scaling theory for the $1/f$ noise

Abstract: We show that in a broad class of processes that show a 1/f α spectrum, the power also explicitly depends on the characteristic time scale. Despite an enormous amount of work, this generic behavior remains so far overlooked and poorly understood. An intriguing example is how the power spectrum of a simple random walk on a ring with L sites shows 1/f 3/2 not 1/f 2 behavior in the frequency range 1/L 2 f 1/2. We address the fundamental issue by a scaling method and discuss a class of solvable processes covering p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Clearly, the power spectrum is a homogeneous function of the arguments, and one can apply the scaling methods [30] to re-express Eq. ( 4) as…”
Section: Spectral Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, the power spectrum is a homogeneous function of the arguments, and one can apply the scaling methods [30] to re-express Eq. ( 4) as…”
Section: Spectral Propertiesmentioning
confidence: 99%
“…In particular, we show intensive analysis for a SOC model, earlier studied by Davidsen and Paczuski [11]. Our main tool of analysis is the scaling method [27][28][29][30] that allows us to understand the spatial correlations by establishing a relationship for temporal correlations between microscopic and macroscopic fluctuations. The paper structure is as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was shown that a certain class of nonlinear Hawkes processes can reproduce power-law distributions [14], which may appeal to practitioners dealing with complex systems exhibiting power-law distributions, such as financial markets. Long-range memory and 1/f β noise (with 0.5 β 1.5), as its characteristic feature [15][16][17][18][19][20], are of particular interest as they are observed across different physical [21][22][23], biological [9] and social systems [24]. Typically long-range memory is modeled using various non-Markovian models: fractional Brownian motion [25][26][27][28][29], ARCH models [30][31][32][33][34][35] or non-Markovian mechanisms such as trapping [36,37].…”
Section: Introductionmentioning
confidence: 99%